Preparing a Historical GIS for the Mass Transit Systems of Metro Manila from the Nineteenth Century to the Present - Damian, Johnson (Kasarinlan: Philippine Journal of Third World Studies; Vol 30, No 2-Vol 31, No 1 (2015-2016): Indigenous People and Contested Access to Land, 2017)
Historical documents in the forms of maps, books, plans, and blueprints reveal functional mass transport systems in Manila long before the present-day rail-transit lines of the city’s metropolitan area. Text bundles from the National Archives of the Philippines provide accounts of Manila’s tramways in the late 1800s to the early 1900s, while transport documents from the 1970s to 1980s contain information on meticulously studied yet discontinued plans regarding Metro Manila’s mass transit system. This research note deals with the processes and challenges of accommodating and piecing together information from these sources together in a geographic information system (GIS). GIS, in turn, is used to create maps to visualize the spatiality, chronology, and evolution of these lines, plans, and their environments. The study focuses primarily on the application of GIS methods to historical transport studies as it seeks to visualize the transport history of Manila, as well as to contribute to the growing literature and set of techniques employed in historical GIS.
Keywords: Historical GIS, urban transport, transport planning, railways